2011
DOI: 10.2106/jbjs.j.00249
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Supramalleolar Osteotomy in Patients with Ankle Osteoarthritis and Varus Deformity

Abstract: Supramalleolar osteotomy is indicated for the treatment of ankle osteoarthritis in patients with minimal talar tilt and neutral or varus heel alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
188
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(205 citation statements)
references
References 13 publications
7
188
1
1
Order By: Relevance
“…Lee et al [41] reported their results in 16 ankles treated with supramalleolar osteotomy combined with fibula osteotomy because of moderate medial ankle osteoarthritis. At the mean follow-up of 2.3 years, substantial functional improvement including AOFAS hindfoot score was observed.…”
Section: Clinical Results Following Supramalleolar Osteotomiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Lee et al [41] reported their results in 16 ankles treated with supramalleolar osteotomy combined with fibula osteotomy because of moderate medial ankle osteoarthritis. At the mean follow-up of 2.3 years, substantial functional improvement including AOFAS hindfoot score was observed.…”
Section: Clinical Results Following Supramalleolar Osteotomiesmentioning
confidence: 99%
“…All radiographic parameters also improved significantly after realignment surgery. The authors have identified that the supramalleolar osteotomy has the best clinical outcome in patients with moderate talar tilt (less than 7.3°) and neutral or varus heel alignment [41]. [37] IV 9 (9 ankles) Six-axis deformity correction using Taylor spatial frame external fixator (9) Superficial pin site infections (2; 22.2 %), delayed union Knupp et al [40] reported their results of realignment surgery in 14 patients treated between 2002 and 2009 because of overcorrected clubfoot deformity.…”
Section: Clinical Results Following Supramalleolar Osteotomiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical realignment procedures can help restore joint function and prevent further progression of asymmetric ankle arthritis [46][47][48][49][50][51][52]. It allows redistribution of the abnormal weight bearing axis on the ankle joint to unload the diseased joint area.…”
Section: Realignment Proceduresmentioning
confidence: 99%